Decline in frequency of the 2La chromosomal inversion in Anopheles gambiae (s.s.) in Western Kenya: correlation with increase in ownership of insecticide-treated bed nets. Issue 1 (December 2016) - Matoke-Muhia, Damaris; Gimnig, John; Kamau, Luna; Shililu, Josephat; Bayoh, M.; Walker, Edward
Abstract Background The 2La chromosomal inversion, a genetic polymorphism inAn. gambiae (sensu stricto ) (s.s .), is associated with adaptation to microclimatic differences in humidity and desiccation resistance and mosquito behaviors. Ownership of insecticide-treated bed nets (ITNs) for malaria control has increased markedly in western Kenya in the last 20 years. An increase in the frequency of ITNs indoors could select against house entering or indoor resting ofAnopheles mosquitoes. Thus, the frequency of the 2La inversion is postulated to change inAn. gambiae (s.s .) with the increase of ITN ownership over time. Methods Anopheles gambiae mosquitoes were sampled between 1994 and 2011 using pyrethrum knockdown, bednet traps and human landing catches (HLC) from Asembo and Seme, western Kenya. The 2La inversion was detected by a PCR assay with primers designed for proximal breakpoints of the 2La/a and 2L+a /+a chromosomal conformation. Mosquitoes were tested for malaria parasite infection by sporozoite ELISA. Results The frequency of the 2La chromosomal inversion declined from 100 % of all chromosomes in 1994 to 17 % in 2005 and remained low through 2011 (21 %). ITN ownership increased from 0 to > 90 % of houses in the study area during this interval. The decline in the frequency of the 2La chromosomal inversion was significantly, negatively correlated with year (r  = -0.93) and with increase in ITN ownership (r  = -0.96). The frequency of the homo- and heterokaryotypes departed significantly from Hardy-Weinberg equilibrium, suggesting that 2La/a karyotype was under selection, earlier in its favor and later, against it. Precipitation and maximum monthly temperature did not vary over time, therefore there was no trend in climate that could account for the decline. There was no significant difference in frequency of the 2La inversion inAn. gambiae (s.s .) females sampled indoors or outdoors in HCL in 2011, nor was there an association between the 2La inversion and infection withPlasmodium falciparum sporozoites. Conclusions The increase in ITN ownership in the study area was negatively correlated with the frequency of 2La inversion. The decline in 2La frequency in western Kenya is postulated to be due to differential impacts of ITNs on mosquitoes with different 2La karyotypes, possibly mediated by differences in behavior associated with the 2La karyotypes. Further research is required to determine if this is a widespread phenomenon, to further determine the association of the 2La karyotypes with mosquito behavior, and to assess whether ITNs are exerting selection mediated by differences in behavior on the different karyotypes.